Teaching in times of COVID-19: determinants of teachers' educational technology use. Issue 5 (3rd September 2021) - Dincher, Matthias; Wagner, Valentin
ABSTRACT: We conduct a large and nationwide survey among German teachers to investigate the determinants of teachers' adaption to an increased use of educational technology during the COVID-19 school closures. We find that higher levels of technical affinity and higher perceived learning effectiveness of distance teaching are positively associated with using at least one (new) educational technology solution while teachers' age and the digital infrastructure of the school have no predictive power.